Structural behaviour of pre-fabricated composite pad footing foundation using cold-formed steel lipped channel sections - Wong, Kah Leong (2010)
Conventional pad footing foundations are built using traditional method of reinforced concrete and utilising wooden formwork. This wooden formwork often encounters problems such as the formation of rectangular shape which is not consistent, the use of timber which is not environmental friendly and not contributing to the strength, the excessive use of labour to construct, and the difficulty to cast during rainy season. As a result, this method tends to slow down the construction time and affect the quality of the product. Thus, an approach to apply the concept of pre-fabrication and composite construction into the construction of pad footing foundation has been introduced by using cold-formed steel (CFS) lipped channel sections to replace both the timber as formwork and steel bars as reinforcement. Currently, the conventional type of foundation is still widely used in local construction, and prefabricated composite pad footing concept is yet to be seen as an alternative usage in foundation systems. In order to investigate the structural behaviours of the pre-fabricated composite pad footing foundation, 18 specimens were tested consisting of 6 specimens of conventional footings, 4 specimens of CFS with A10 wire mesh as reinforcement, and 8 specimens of fully CFS with thickness varies from 150 mm to 200 mm, and length varies from 1000 mm to 1750 mm. All specimens were checked for punching shear, longitudinal shear, and bending moment. The experimental and theoretical calculations were carried out and comparisons were made. The results show good agreement between the experimental works and theoretical values with flexural and shear strength are much higher than the conventional pad footing. Therefore, it can be concluded that the proposed pre-fabricated composite pad footing foundation using CFS lipped channel sections is suitable to be used as pad footing.